The Relationship Between School-Based Research and Preschool Teachers’ Teaching Ability: The Mediating Role of Constructivist Beliefs in Teaching - Yan, Zhonglian; Zhao, Shoumei (Frontiers in Psychology, 2022)
To understand the relationship between kindergarten school-based research (SBR) and preschool teachers’ teaching ability and identify the mechanism by which SBR affects teachers' teaching ability, a survey of randomly sampled preschool teachers in Sichuan Province (N=625, Mage=26.61) was conducted online using three scales assessing community learning, teaching ability and teaching philosophy. The survey results showed that the level of SBR reached the upper-middle level. The level of SBR positively predicted the teaching beliefs and teaching ability of preschool teachers. SBR influenced teaching ability through direct and indirect effects, with indirect effects accounting for 23.5% of the total effect; however, only constructivist teaching beliefs played a mediating role in the relationship between SBR and teaching ability via an indirect effect. SBR focused on improvement in teaching ability should not only examine the connection between SBR and practical problems to promote improvement in teachers’ teaching ability but also should examine the role of teachers' beliefs and influence teachers' teaching abilities by changing teachers' teaching beliefs.